TUHER 2022
DOI: 10.58653/nche.v10i1.10
|View full text |Cite
|
Sign up to set email alerts
|

Talent Management: The Game Changer for Work Engagement of Non-Teaching Workforce at Kyambogo University, Uganda

Abstract: The challenge in public universities in Uganda is that university non-teaching staff are disengaged and take their jobs for granted, hence never make an effort to serve to the satisfaction of students and other stakeholders. This study examined whether talent management strategies employed by the universities were a game changer for work engagement of the non-teaching workforce in public universities. Specifically, the study tested whether talent management in terms of talent attraction, talent development and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…At Kyambogo University, middle-level academic leadership also exhibits a lack of leadership competence by failing to effectively supervise those under them (Kasule, 2020). According to Mugizi et al (2022), Kyambogo University experienced maladministration, decadence in governance, a lack of ethics, and incompetence among leaders. The contextual circumstances above indicate that academic staff organisational commitment was low, as well as job satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…At Kyambogo University, middle-level academic leadership also exhibits a lack of leadership competence by failing to effectively supervise those under them (Kasule, 2020). According to Mugizi et al (2022), Kyambogo University experienced maladministration, decadence in governance, a lack of ethics, and incompetence among leaders. The contextual circumstances above indicate that academic staff organisational commitment was low, as well as job satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…These challenges range from inadequate resources, limited professional development opportunities, bureaucratic hurdles, and sometimes insufficient recognition for their contributions (Nakimuli, 2023;Najjum, Gallagher & Nambi, 2022). Despite these critical roles, non-teaching staffs face challenges that make them non commital to their tasks (Mugizi, et al 2022). Before Kenya gained independence in 1963, there were only a few educational institutions, primarily missionary schools, which laid the foundation for higher education in the country.…”
Section: Introductionmentioning
confidence: 99%
“…In a study done at KYU, Namubiru et al (2017) indicated that the problems of KYU staff were a result of poor leadership because of the lack of a shared vision between staff and the leaders of the university. According to Mugizi et al (2022), the university suffered maladministration, decadence in governance, and unethical and negligent behaviours. Thus, this study was attracted to how the leadership behaviours of the university leaders influenced the job satisfaction of academic staff at Kyambogo University.…”
Section: Introductionmentioning
confidence: 99%